Environmental Science and Pollution Research - Springer (Springer, 2026)
Environmental Science and Pollution Research (ESPR) serves the international community in all areas of Environmental Science and related subjects with emphasis on chemical and environmental stressors. Covers all areas of Environmental Science and related subjects. Publishes on the natural sciences, but also includes the impacts of legislation and regulation on pollution control. Safeguards international and interdisciplinary character through a global network of editorial board members. Official publication of the EuCheMS Division of Chemistry and the Environment. Authors from participating institutions can publish Open Choice at no cost.
Keywords: Ciencias ambientales; Contaminación; Revistas depredadoras; Predatory journals